2023
DOI: 10.1126/sciadv.adf4144
|View full text |Cite
|
Sign up to set email alerts
|

Cx26 heterozygous mutations cause hyperacusis-like hearing oversensitivity and increase susceptibility to noise

Abstract: Gap junction gene GJB2 (Cx26) mutations cause >50% of nonsyndromic hearing loss. Its recessive hetero-mutation carriers, who have no deafness, occupy ~10 to 20% of the general population. Here, we report an unexpected finding that these heterozygote carriers have hearing oversensitivity, and active cochlear amplification increased. Mouse models show that Cx26 hetero-deletion reduced endocochlear potential generation in the cochlear lateral wall and caused outer hair cell electromotor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…ABR was evoked by different frequencies of sound (clicks, 8, 16, and 32 kHz) through the closed-field speaker. As the lowest level at which a visual waveform response could be observed, the ABR threshold was defined ( Liu et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…ABR was evoked by different frequencies of sound (clicks, 8, 16, and 32 kHz) through the closed-field speaker. As the lowest level at which a visual waveform response could be observed, the ABR threshold was defined ( Liu et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Mice were awake in a small cage under loud-speakers in a sound-proof chamber and exposed to white-noise (95-98 dB SPL) for 2 h, one time. The sound pressure level and spectrum in the cage were measured prior to placement of the animal (Zhao et al, 2021(Zhao et al, , 2022Liu et al, 2023). For each time of noise exposure, 2-4 mice were exposed and randomly separated to treatment groups and control group to ensure age-matched control and background noise control among the experimental groups.…”
Section: Noise Exposure and Drug Administrationsmentioning
confidence: 99%
“…ABR was recorded by use of a Tucker-Davis R3 workstation with ES-1 high frequency speaker (Tucker-Davis Tech. Alachua, FL) (Zhu et al, 2013(Zhu et al, , 2015Mei et al, 2017;Zhao et al, 2022;Liu et al, 2023). ABR was recorded by stimulation with clicks in alternative polarity and tone bursts (4-40 kHz) from 80 to 10 dB SPL in a 5 dB step in a double-walled sound isolation room.…”
Section: Auditory Brainstem Response and Distortion Product Otoacoust...mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also found that children who carry a single-point heterozygous mutation in the gap junction (GJ) gene Cx26 (GJB2) are susceptible to noise, which eventually leads to hearing loss (HL). 1 …”
mentioning
confidence: 99%